Observer‐Based Multiple Faults Diagnosis Scheme for Satellite Attitude Control System. Issue 1 (20th July 2018) - Gao, Sheng; Zhang, Wei; He, Xu
Abstract: This paper proposes a multiple fault diagnosis (MFD) scheme based on an observer method for satellite attitude control systems (ACSs) subject to nonlinearity and external disturbances of the system. The essential idea is to develop a fault diagnosis scheme and design the corresponding observers for satellite ACSs. The nonlinearity, space external disturbances, sensor uncertainties, and multiple faults problem of the satellite ACS are all taken into account. The proposed MFD scheme is developed at two different levels. First, at the system level, two nonlinear observers based on analytical redundancy are designed for the MFD of the satellite ACS; this level roughly reveals the fault source. Then, at the component level, a bank of sliding mode observers activated by the results of the previous diagnosis is designed to precisely diagnose multiple faults of actuators in the satellite ACS; this level further precisely reveals the fault source. Both the nonlinear observers and the sliding mode observers are confirmed to be asymptotically stable via Lyapunov stability theory. Finally, numerical simulations of a satellite ACS are performed to illustrate the effectiveness of the proposed MFD scheme.